PRODUKTIVITAS PENANGKAPAN IKAN PELAGIS BESAR MENGGUNAKAN PANCING ULUR YANG BERPANGKALAN DI KABUPATEN MAJENE (Large Pelagic Fisheries Productivity by Using Handline Based in Majene District) - Alfa FP. Nelwan; . Sudirman; Mukti Zainuddin; Muh. Kurnia (Bogor Agricultural University, 2015)
——-ABSTRACTLarge pelagic fish is a fishery commodity which has a high economic value, so its development can improve the economy of communities and regions. The aim of this study was to determine the fishing productivity of large pelagic fisheries using handline. This research was conducted in July until September 2012. This study examines the fishing productivity of handling with operated by a fisherman in Majene district, West Sulawesi. Fishing activity utilizing FADs as a fishing ground. Fishing Productivity was obtained from the weight ratio of the amount of catches and duration of fishing time. Fishing productivity is determined for each type of fish catches, namely skipjack tuna (Katsuwonus Pelamis), yellowfin tuna (Thunnus albacares), and mackerel tuna (Auxis thazard). The proportion of the total catches of skipjack tuna showed greater than other fish species. The relationship between fishing productivity with the time fishing is declining with increasing duration of time fishing. Cluster analysis showed that there are two clusters of fishing productivity for 23 fishing activity. Fishing ground with the largest production was in the FADs in 118031'44,8''E and 118Â°34'16.0